1983
DOI: 10.1190/1.1441515
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of Love wave propagation

Abstract: Love wave propagation is studied by investigating numerical modeling results for several examples of geologic interest. The modal characteristics of the results are clarified by the use of narrow band‐pass filters and two‐dimensional Fourier transforms in range and time. Such processing makes it possible to study changes in phase and group velocity for the various modes and to locate points of reflection. This permits one to gain insight into changes in the physical properties of the surface channel supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Rayleigh waves are not explicitly considered as they d o not satisfy the excitation-time imaging condition; they may be implicitly included (as described above) if they are not so large that they destabilize the solution. [In contrast, Sun & McMechan (1991) demonstrated that SH velocities are imagable using Love wave data because they may be thought of as multiples in a surface waveguide (Kelly 1983) and so explicitly satisfy the same imaging condition as primary SH reflections.] We defer application to field data until the full 3-D algorithms are developed; this is now in progress [cf.…”
Section: Discussion a N D Synopsismentioning
confidence: 99%
“…Rayleigh waves are not explicitly considered as they d o not satisfy the excitation-time imaging condition; they may be implicitly included (as described above) if they are not so large that they destabilize the solution. [In contrast, Sun & McMechan (1991) demonstrated that SH velocities are imagable using Love wave data because they may be thought of as multiples in a surface waveguide (Kelly 1983) and so explicitly satisfy the same imaging condition as primary SH reflections.] We defer application to field data until the full 3-D algorithms are developed; this is now in progress [cf.…”
Section: Discussion a N D Synopsismentioning
confidence: 99%
“…Although early results on elastic wavefield modeling have been obtained long ago [42][43][44] however, they were rather qualitative because of a large step of the space mesh h = 1/5k Ä 1/2k. Considerably increased computer performance and also development of multiprocessor computer systems have made it possible to increase the calculation accuracy [45][46][47].…”
Section: Solid Layer Over Solid Half Spacementioning
confidence: 99%
“…It remains only to check that each eigenvalue is simple and to compute the corresponding eigenfunction. For this it suffices to remark that, when (K~, 42) is a solution of (20), then the set of solutions of the homogeneous system (17) in (A~, A2) is a one dimensional space. A particular solution is given by:…”
Section: Tpiq(k)=as(k)cos(k~(kh)qh)e-~itk'h)l O=nmentioning
confidence: 99%
“…The analysis of the approximation of these waves is of course of great importance since their presence affects the geophysical measures which are made at the surface. In a recent paper [17], Kelly presented numerical computations in which he looked at the approximation of these waves. Our goal in this paper is to deal with theoretical analysis of this problem.…”
Section: Introductionmentioning
confidence: 99%